P243 Are healthcare professionals aware of costs of respiratory inhalers?. (19th November 2012) - Mak, V; Marlow, H; Restrick, L; Porter, A
Abstract : Introduction: In 2011, 3 of the top 5 most expensive drugs to the NHS were respiratory inhalers, the most expensive being Seretide 250 evohaler. To achieve best value from our respiratory spend, healthcare professionals (HCPs) should know the relative costs of inhalers, and that their patients are using these devices appropriately. We undertook a survey of HCPs to test their knowledge of respiratory inhaler cost and how well the devices are used. Methods: We created a Survey Monkey questionnaire concerning the costs of commonly prescribed respiratory inhalers (see table ) allowing respondents to click on an approximate range of costs for one month's treatment at normal recommended dose. We also asked about awareness of the evidence for effective use of metered dose inhalers (MDIs) by patients and HCPs. The survey was disseminated by email from various databases in community and hospital care within NHS London and beyond, especially to those involved in respiratory care. Results: There were 1274 respondents, 21% were doctors, 38% nurses, 21% pharmacists and 15% allied healthcare professionals (AHPs), 70% had a respiratory interest and 89% were clinicians. Overall, the correct price range was identified by fewer than 50% of all respondents for the inhalers tested (except generic salbutamol), the worst being for Seretide 250 evohaler and Ventol in evohaler (see table ). 76% of respondents were not aware that fewer than 10% of patients can use an MDI effectively and 87% were not aware that fewer than 10% of HCPs can demonstrate the correct use of an MDI. Having attended a London Respiratory Team (LRT) event significantly improved the correct response rate (see table ). Conclusions: Most HCPs are not aware of the costs of inhalers and how poorly some inhalers are used. Increasing awareness of cost could add a sense of value and improve responsible prescribing, including renewed focus on stepping down patients on high potency treatments when they are stable or have experienced no benefit, and always using a spacer with an MDI. Knowledge of which inhalers provide best value is also important for prescribers when choosing between evidenced based alternatives.